Periglacial features in the vicinity of Tiffindell Ski Resort, North East Cape Drakensberg, South Africa, and their implications for the development of the resort - Kück, Karen Melody (Rhodes University, Faculty of Science, Department of Geography, 1997)
This thesis provides a description of the periglacial environment and features in the vicinity of Tiffindell Ski resort, on the slopes of Ben MacDhui (3001.2m.), the highest point of the East Cape Drakensberg, South Africa. Active and inactive periglacial features were located, mapped and described. Of particular interest were periglaciar slope deposits including gelifluction turf-banked lobes and stone lobes, and cryoturbation features including polygons and thufur. Local environmental factors, such as aspect, moisture, topography, soil texture and depth of freezing, appear to act as important controls on the spatial distribution of the periglacial features. Identification and quantification of periglacial processes in the regolith was investigated using temperature and soil moisture sensors coupled to dataloggers. Research was undertaken over a 16 month period from June 1995 to September 1996 so that comparisons between the winter conditions of 1995 and 1996 could be drawn. The Tiffindell area was observed to be characterised in the winter months by 'diurnal freezethaw days', as well as by 'ice days', 1996 experiencing colder temperatures than 1995. With more than 78% of the days from May to September 1996 being 'ice days', and simultaneously experiencing high soil moisture contents, freezing penetration to a depth of greater than 0.2m was observed to occur in the Tiffindell area, causing frost heave and gelifluction. The summer thaw of ice lenses that developed in the cold winter months caused surface movement downslope of gelifluction lobes of up to 39mm over an 18 month period, although movement declined rapidly with depth and was essentially restricted to the uppermost 130mm of the regolith. Other features such as sorted and non-sorted polygons and thufur were identified and found to be active under the present climatic conditions and depth of frost penetration at Tiffindell. Stone lobes were identified on the south and southeast-facing slopes at Tiffindell, but are apparently inactive under present climatic conditions. Their existence suggests the presence of severe seasonal frost in the past. The implications of the air and ground surface temperatures, and of seasonal frost penetration for the development of Tiffindell Ski resort were considered, and suggestions regarding their economic significance are presented.
Keywords: Tiffindell Ski Resort (South Africa); Slopes (Physical geography) -- South Africa -- Eastern Cape; Landforms -- South Africa -- Eastern Cape; Climatic geomorphology -- South Africa -- Eastern Cape; Drakensberg Mountains